2017
DOI: 10.1021/acs.nanolett.6b04825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Morphology and Magnetic Impurities on the Electronic Structure in Cobalt-Doped BaFe2As2Superconductors

Abstract: Combined scanning tunneling microscopy, spectroscopy and local barrier height (LBH) studies show that low-temperature-cleaved optimally-doped Ba(Fe 1-x Co x ) 2 As 2 crystals with x=0.06, with T c = 22 K, have complicated morphologies. Although the cleavage surface and hence the morphologies are variable, the superconducting gap maps show the same gap widths and nanometer size inhomogeneities irrelevant to the morphology. Based on the spectroscopy and LBH maps, the bright patches and dark stripes in the morpho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…At the temperature of experiments in this work (4 K), Cr-122 has a G-AFM ground state (TN~ 100 K); optimally doped Co-122 is in SC state (Tc ~ 22 K) 24 ; and the composition of the Ni-122 was picked to locate it in the coexistence range of SC and AFM orders (Tc ~ 19 K, TN~ 45 K). After low temperature cleavage, the three sets of samples show similar topography, which is the coexistence of As terminated 2×1 and Ba terminated √2 × √2 reconstructions, as reported for Co-122 before 25 . Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…At the temperature of experiments in this work (4 K), Cr-122 has a G-AFM ground state (TN~ 100 K); optimally doped Co-122 is in SC state (Tc ~ 22 K) 24 ; and the composition of the Ni-122 was picked to locate it in the coexistence range of SC and AFM orders (Tc ~ 19 K, TN~ 45 K). After low temperature cleavage, the three sets of samples show similar topography, which is the coexistence of As terminated 2×1 and Ba terminated √2 × √2 reconstructions, as reported for Co-122 before 25 . Fig.…”
Section: Resultssupporting
confidence: 70%
“…The above coexistence of S-shape and in-gap states with superconducting states are not affected by the surface termination; they are also observed on 2 × 1 surfaces. A STM study of BaFe2As2 has found both √2 × √2 and 2 × 1 surface reconstruction coexistence on the cleavage surface 25,27 . As reported recently, although different terminations with different LDOS coexist on the surface of the transition metal substituted BaFe2As2 (√2 × √2 and 2 × 1), the superconductivity gap width is not affected by the surface reconstructions owing to the global nature of the superconductivity 25 .…”
Section: Resultsmentioning
confidence: 99%
“…To visualize the local superconductivity, a superconducting gap map serves better than an STS dI/dV map. As an example, Figure 3 shows a STM topographic image and corresponding superconducting gap map, which is calculated from the current imaging tunneling spectroscopy (CITS) image at 4.2 K [11,12]. The majority area of the sample does not show superconductivity, which is consistent with a low superconducting volume fraction from the bulk measurement (about 3%).…”
Section: Resultsmentioning
confidence: 64%
“…However, these Pr dopants, in parallel, create lattice defects with some net magnetic moment [18]. The local magnetic moment can also destroy superconductivity [11]. Therefore, the Pr-Ca122 sample is not able to become a bulk superconductor by simply increasing the Pr dopant concentration.…”
Section: Resultsmentioning
confidence: 99%
“…3. Using a similar method as STM report on Co-doped BaFe2As2 [37], the 2 × 1 and √2 × √2 reconstructed surfaces can be assigned to arsenic termination and europium termination, respectively, as shown in Fig. 3a.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 97%